2019
DOI: 10.11114/jets.v7i3.4047
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Composition and Jumping Performance of Volleyball Players

Abstract: Body composition and the skill of jumping are very important for high physical performance in volleyball. The purpose of this study is to analyze the relationship between body composition and jumping performance in female volleyball players aged 14-17. 74 female volleyball players volunteered to participate in the study. The height, body weight, body mass index, body fat percentage, body muscle mass and trunk fat percentage measurements were taken and the vertical jump and standing long jump tests were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
4
5
1
2
Order By: Relevance
“…The main findings of the current study found a significantly low correlation between somatotype characteristics and certain general physical fitness tests and throwing velocity. During the verification process between somatotype variables and general physical fitness tests and throwing velocity, the findings of the current study concur with other published studies in handball and volleyball, where higher endomorphy corresponds to less power in the lower limbs, reduced cardiopulmonary capabilities and hence lower sprint performance 30,31 . Endomorphy is characterized by a higher percentage of body fat 19 and for the optimum performance of a handball player, the percentage of body fat must be within the recommended figures 32 .…”
Section: Discussionsupporting
confidence: 91%
“…The main findings of the current study found a significantly low correlation between somatotype characteristics and certain general physical fitness tests and throwing velocity. During the verification process between somatotype variables and general physical fitness tests and throwing velocity, the findings of the current study concur with other published studies in handball and volleyball, where higher endomorphy corresponds to less power in the lower limbs, reduced cardiopulmonary capabilities and hence lower sprint performance 30,31 . Endomorphy is characterized by a higher percentage of body fat 19 and for the optimum performance of a handball player, the percentage of body fat must be within the recommended figures 32 .…”
Section: Discussionsupporting
confidence: 91%
“…However, if we would compare the results of muscle mass in Turkish volleyball players by Acar & Eler (2019) 24.9 ± 3.0 kg and muscle mass results in Spanish players by Martín-Matillas et al (2014) 27.3 ± 2.9 kg, we will conclude that both national teams of Montenegro and Kosovo also has greater or approximately the same values. The t-test results show that Montenegro and Kosovo players are approximately the same when it comes to years, as well as that the Montenegrin female volleyball players had higher values of height and body mass than those playing for the selection of Kosovo.…”
Section: Discussionmentioning
confidence: 94%
“…Bodyweight, fat mass, and muscle mass are important anthropometric factors to support jumping performance. 9 To get a high vertical jump value, maximum muscle contraction is required. The main structure of skeletal muscle is the myofibrils which are an important unit of skeletal muscle, contain contractile protein elements that cause muscles to contract.…”
Section: Discussionmentioning
confidence: 99%